The epidemiology of malaria in Prábis, Guinea-Bissau - Aldina Gonçalves; Paulo Ferrinho; Francisco Dias (Memorias do Instituto Oswaldo Cruz, 1996)
This article reports upon a community survey of malaria in Prábis, Guinea-Bissau. A house to house census of the population was initially carried out from August to December 1991(rainy season). After completing the census of each village, the population was invited to come, a week later, to a central point, where they were medically examined and finger-prick blood samples were collected for epidemiological characterization of the malaria situation in the area. The blood films of the one single village were used to compare the sensitivity and specificity of Polymerase Chain Reaction (PCR) with optical microscopy detection of parasites. In another village, the occurrence of parasitaemia was compared in children with and without fever. During the dry season, from March to June 1992, the population in each village was again invited to come to a central point. Some of the field procedures were repeated. The study revealed Prábis as an administrative Sector of Guinea-Bissau with endemic malaria, mostly due to Plasmodium falciparum, but with a significant rate of mixed infections. Active transmission occurred throughout the year, but it was more intensive during the rainy season and in the northwestern quadrant of the Sector. The level of endemicity of the villages varied from hypo to holoendemic. The factors associated with the differences among villages included village size and predominant economic activity (closeness to rice fields). The transmission paradigm was, most likely, a mixture of malaria of the African wet Savannah and malaria associated with irrigated paddy fields. PCR proved to be a sensitive method with low specificity during the dry season. Pyraexia of 37.4ºC or higher in children aged 2-9 years is not a sensitive indicator of parasitaemia but, it is highly specific and it has a clinically useful predictive value.